The effect of residual palladium on the performance of organic electrochemical transistors - Griggs, Sophie; Marks, Adam; Meli, Dilara; Rebetez, Gonzague; Bardagot, Olivier; Paulsen, Bryan D.; Chen, Hu; Weaver, Karrie; Nugraha, Mohamad I.; Schafer, Emily A.; Tropp, Joshua; Aitchison, Catherine M.; et al. (Nature communications, 2022)
Organic electrochemical transistors are a promising technology for bioelectronic devices, with applications in neuromorphic computing and healthcare. The active component enabling an organic electrochemical transistor is the organic mixed ionic-electronic conductor whose optimization is critical for realizing high-performing devices. In this study, the influence of purity and molecular weight is examined for a p-type polythiophene and an n-type naphthalene diimide-based polymer in improving the performance and safety of organic electrochemical transistors. Our preparative GPC purification reduced the Pd content in the polymers and improved their organic electrochemical transistor mobility by ~60% and 80% for the p- and n-type materials, respectively. These findings demonstrate the paramount importance of removing residual Pd, which was concluded to be more critical than optimization of a polymer’s molecular weight, to improve organic electrochemical transistor performance and that there is readily available improvement in performance and stability of many of the reported organic mixed ionic-electronic conductors. The optimization of organic mixed ionic-electronic conductor is critical to realize high performance organic electrochemical transistors. Here, the authors demonstrate the removal of residual palladium impurities to be the key factor to achieving a figure-of-merit of [μC*] of over 2000 V −1 cm −1 s −1 .